mean......

Asked by harshitalohia | 5th Feb, 2010, 08:05: PM

Expert Answer:


(z - x1) + (z - x2) +..........(z - x20) =

(z+z...+z...20 times) - (x1 + x2 +....+x20) =

(20z) - 20((x1 + x2 +....+x20)/20) =                        .............Multiply and divide by 20 in the second 'x' terms.

(20z) - 20(z) = 0  ........................since z = (x1 + x2 +....+x20)/20

Regards,

Team,

TopperLearning.

 

Answered by  | 6th Feb, 2010, 10:18: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.